2013
DOI: 10.5194/nhess-13-1457-2013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing gridded observations for daily precipitation extremes in the Alps with a focus on northwest Italy

Abstract: In this study we compare three gridded observed datasets of daily precipitation (EOBS, MAP and NWIOI) over the Great Alpine Region (GAR) and a subregion in northwest Italy (NWI) in order to better understand the past variability of daily climate extremes and to set up a basis for developing regional climate scenarios. The grids are first compared with respect to their temporal similarity by calculating the correlation and relative mean absolute error of the time series. They are then compared with respect to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…The election of this gridded data set is based on the abundant scientific literature using E-OBS for the evaluation of regional climate models (e.g., Costa et al, 2012;Jiménez-Guerrero et al, 2013;Turco et al, 2013;Ceglar et al, 2014, among many others). However, several authors highlight the E-OBS limitations.…”
Section: Observational Databasementioning
confidence: 99%
“…The election of this gridded data set is based on the abundant scientific literature using E-OBS for the evaluation of regional climate models (e.g., Costa et al, 2012;Jiménez-Guerrero et al, 2013;Turco et al, 2013;Ceglar et al, 2014, among many others). However, several authors highlight the E-OBS limitations.…”
Section: Observational Databasementioning
confidence: 99%
“…Flaounas et al (2012) validated the E-OBS dataset in the Mediterranean region and found that those data must be used with care in complex environments such as coastal areas and mountainous regions. Turco et al (2013b) compared three different gridded datasets in the greater Alpine region (E-OBS and two local grids) and found that specific regional products are often more trustworthy than E-OBS. Herrera et al (2012) compared Spain02 and E-OBS in Spain and found that the station density severely affects the results.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for precipitation data sets in complex orography areas like the Alps: in fact, the analysis performed by Turco et al [2013] showed that E-OBS cannot be used for spatial climatology of extreme precipitation indices over the Alpine region. Moreover, the spatial resolution of CRU and E-OBS data sets (respectively, about 60 and 28 km) could not be adequate to properly validate precipitation fields from climate simulations at less than 10 km resolution.…”
Section: Introductionmentioning
confidence: 99%